Fenomena Disinformasi Vaksinasi Covid-19 pada Remaja di Kabupaten Jombang - tyvani audia rizki; Widhiadi Yoga Sembada; Utih Amartiwi (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2024)
This study looks at how disinformation regarding Covid-19 affects the process of making vaccination decisions for adolescents aged 12 to 17 years in Jombang Regency. The increase in the spread of disinformation related to Covid-19, which contains information that lacks credibility in the content of the information available, creates various negative perspectives from its readers towards the Covid-19 vaccination, which, as stated by WHO, has spread disinformation and caused confusion, suspicion, as well as negative sentiment towards the Covid-19 vaccination. In addition to vaccine skepticism and skepticism, public health has long been the target of foreign disinformation campaigns, including conspiracy theories, as part of the larger struggle for national security (Boghardt, 2009; Ellick & Westbrook, 2018). With the influence of rampant disinformation on various social media, the suspicion of vaccination is increasing, which gives a negative view. This study used a qualitative approach with a phenomenological study method. Data collection techniques were carried out by means of FGD (Forum Group Discussion) and interviews. The results of the study show that Covid-19 disinformation has a role in the decision-making process for youth vaccination aged 12-17 years in Jombang. However, with this, there are still other factors that influence the decision, namely related to the role of community leaders around. This study used a qualitative approach with a phenomenological study method. Data collection techniques were carried out by means of FGD (Forum Group Discussion) and interviews. The results of the study show that Covid-19 disinformation has a role in the decision-making process for youth vaccination aged 12-17 years in Jombang Regency. However, with this, there are still other factors that influence the decision, namely related to the role of community leaders around. This study used a qualitative approach with the phenomenological study method. Data collection techniques were carried out by means of FGD (Forum Group Discussion) and interviews. The results of the study show that Covid-19 disinformation has a role in the decision-making process for youth vaccination aged 12-17 years in Jombang Regency. However, with this, there are still other factors that influence the decision, namely related to the role of community leaders around. Keywords: Disinformation; Vaccination; Decisions